Supporting Service-Learning in an Existing Curriculum - Kim Hawkins; Julie Rabun; Jeff Knox (Academic Chairpersons Conference Proceedings, 2017)
This group presentation is interactive and provides a solution-based approach to service-learning. Participants may be involved in a variety of ways such as taking part in small-group activities, role playing, case studies, simulations, problem solving or other hands-on instructional activities and will leave with service-learning ideas for their course(s).
Keywords: service-learning; undergraduate curriculum; community involvement; student engagement; civic engagement